Find The Derivative Of The Functionf(x)= 1/7 X^7+(

TheIntegral

From: US
Posts: 26
Votes: 104
Find the derivative of the function f(x)= 1/7 x^7+(x^2+6)(x^2-x-6)+27 a. f(x)=7x3-15x-2 b. f(x)=x3+3x2+4 c. f(x)=4x6+7 d. f(x)=x6+4x3-3x2-6

 

Answer No.1

MythGenius90

From: US
Posts: 42
Votes: 84
You will need to know these formulas: (d/dx)(x^n) = nx^(n-1) (d/dx)(f(x) + g(x)) = f'(x) + g'(x) (d/dx)(f(x) - g(x)) = f'(x) - g'(x) (d/dx)(f(x)g(x)) = f'(x)g(x) + f(x)g'(x) f'(x) = (1/7)(7)x^6 + 2x(x^2 - x - 6) + (x^2 + 6)(2x - 1) = x^6 + 2x^3 - 2x^2 - 12x + 2x^3 - x^2 + 12x - 6 = x^6 + 4x^3 - 3x^2 - 6 which is d PLEASE RATE LIFESAVER if this helps you. THANKS.

Answer No.2

Anonymous

From: -
Posts: -
Votes: -
Well let's simplify the equation first and go from there. Thanks a funky looking equation so well try and get rid of the parts in parenthesis. f(x) = (1/7)x^7 + (x^4-x^3-6x^2+6x^2-6x-36) + 27 Now -6x^2 and + 6x^2 cancel and -36 can be combine with 27 so we are left with.... f(x) = (1/7)x^7 + x^4 - x^3 - 6x -9 That's much easier to derive. So the answer unsimplified will look like... f'(x) = 7*(1/7)x^6 + 4x^3 - 3x^2 - 6 - 0 So pick the answer choice closest to that. Remember, before you try to derive or integrate you can always do things like simplify the expression or even break it up into smaller more manageable parts.

Your Comment/Solution

Post As: Anonymous [Change]
Enter